Alcohol Plus Additional Risk Factors: Rodent Model of Liver Injury - Wu, Qixiang; Yang, Dashuai; Liu, Chixiang; Xu, Tao (Seminars in Liver Disease, 2024)
Alcohol-associated liver disease (ALD), primarily caused by chronic excessive alcohol consumption, is a leading cause of chronic liver disease worldwide. ALD includes alcohol-associated steatotic liver, alcohol-associated hepatitis (AH), fibrosis, cirrhosis, and can even progress to hepatocellular carcinoma (HCC). Existing research indicates that the risk factors of ALD are quite numerous. In addition to drinking patterns, factors such as aldehyde dehydrogenase 2 (ALDH2) deficiency, smoking, medication administration, high-fat diet (HFD), hepatitis virus infection, and disruption of circadian rhythms can also increase susceptibility to ALD. However, there is limited understanding regarding the exacerbation of liver injury by alcohol plus additional risk factors. This review presents rodent models of EtOH + “X,” which simulate the synergistic effects of alcohol and additional risk factors in causing liver injury. These models offer a further exploration of the interactions between alcohol and additional risk factors, advancing the simulation of human ALD and providing a more reliable platform for studying disease mechanisms and exploring therapeutic interventions. We summarize the modeling methods, relevant indicators of liver injury, and focus on the targets of the synergistic effects as well as the associated mechanisms.
Keywords: alcohol consumption; ALD; MetALD; animal model; liver injury